👤

Rozwiąż równania. Zacznij od uproszczenia wyrażenia występującego po lewej stronie równania.
a) 5x - 7x = 2
b) 9x - 8x + 2 = 5
c) 7x + 4 - 8x = 0
d) 42 + 4x - x = 12
e) y - 4 + y = 6
f) 1/2z + 4x - x = 12


Odpowiedź :

a) -2x=2

x=-1

b) x=5-2

x=3

c)-x=0-4

-x=-4

x=4

d) 3x=12-42

3x=-30

x=-10

e) 2y=6+4

2y=10

y=5

f) nw czy to z?

Odpowiedź:

a) 5x- 7x=2

    -2x=2/:2

       x=-1

b)9x-8x+2=5

     x+2=5

      x=5-2

      x=3

c)7x+4-8x=0

  -x+4=0

   -x=-4

     x=4

d)42+4x-x=12

42+3x=12

3x=12-42

3x=-30

x=-10

e) y-4+y=6

2y-4=6

2y=6+4

2y=10

y=5

f)1/2z+4x-x=12

1/2+3x=12

z+6x=24

z=24-6x

Szczegółowe wyjaśnienie: